Recurrent Hidradenocarcinoma in the Abdominal Wall with no Distant Metastasis: A Case Report and Literature Review - Al-Ani, Yahia Hameed; Al-Ani, Raid M.; Nori, Wassan; Al-Sudani, Israa Mahdi (Diyala Journal of Medicine, 2025)
Background: Hidradenocarcinoma is a rare, aggressive tumor with a high rate of local recurrence and distant metastasis. There are no current management guidelines, and surgery has been used to control the primary disease. Even with wide surgical excision, the course of the tumor is unpredictable, and the prognosis for survival is poor. The most common location is the scalp, followed by the extremities, and rarely the trunk. Objective: To present a rare recurrent hidradenocarcinoma in the abdominal wall with no distant metastasis. Case presentation: We present a rare case of recurrent hidradenocarcinoma on the abdominal wall in a 56-year-old male with no known distant metastasis treated with wide surgical excision. Conclusion: This case represents the second reported case of hidradenocarcinoma involving the abdominal wall in the literature. Wide surgical excisions of the tumor with wide safe margins carry excellent outcomes on 5-year follow-up. Keywords: Recurrent hidradenocarcinoma; Abdominal wall hidradenocarcinoma; Distant metastasis; Case report.